ROUTING OF VEHICLES USING THE METAHEURISTIC ALGORITHM - Nurserik Д.; Gusmanova Ф.Р.; Abdulkarimova Г.А.; Dalbekova Қ.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The main goal of the proposed research is to solve the problem of vehicle routing using genetic algorithms. Vehicle Routing Problem (VRP) is an NP-complete complex combinatorial problem. With a large amount of input data in a VRP problem, it is very expensive to find the most optimal solution. Genetic algorithms offer the most optimal solution in a short period of time. This article discusses genetic algorithms based on the mechanism of evolution for finding the optimal route by metaheuristic methods. The aim of the work is to minimize the time needed to find the most acceptable optimal solution to the problem, as well as to develop metaheuristic methods.